Studi Penggunaan Energi pada Implementasi Protokol Routing RPL dan LOADng di Wireless Sensor Network - Rozali Syahputra; Reza Andria Siregar; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wireless Sensor Networks can generally interpret as wireless networks that are distributed using embedded devices equipped with sensor nodes. The sensor node has limited resources that are equivalent to two AA type batteries. Some of the things that spend more energy on WSN are Package Control in the WSN routing. Routing over Low Power and Lossy Network (RPL) is one of the protocols used for routing WSN networks. However, in some cases, it is necessary to use other protocols as an alternative. Light On-demand Ad hoc Distance-vector Routing (LOADng) is the right lightweight protocol for RPL alternative. Both of this protocol then implemented in several topology scenarios and is also on node placement factor, radio transmission distance, and control package for each node affecting the RPL and LOADng protocol's energy consumption. From this study, the results obtained for the Package Control scheme around reducing energy consumption by an average of 19% for the RPL protocol with Imin changes 4 seconds to 8 seconds and then cutting the average energy consumption by 14% for LOADng with changes in Route Hold Time from 5 minutes to 10 minutes.